Economic Impact Analysis of Reclamation Activities on Rampus (Gillnet) Fishery in Kaliadem, Muara Angke, North Jakarta - Kusumastanto, Tridoyo; Sobirin, Akhmad; Nababan, Benny Osta; Indah, Mega Natasha (Coastal and Ocean Journal (COJ), 2025)
The Jakarta Bay reclamation has impacted capture fisheries, such as rampus (gillnet) fishermen in Kaliadem. This study aims to analyze the economic impacts of reclamation including its adaptation strategies, fishing business unit feasibility, fishermen’s welfare, and post-reclamation policy options. Data were collected through surveys and a census and analyzed using analyses of spatial characteristics, feasibility, Fishermen Exchange Rate (NTN), qualitative description, and policy alternatives. The results indicate that the primary fishing grounds of rampus fishermen are directly affected by reclamation. The fishing units remain viable both before and after reclamation. Fishermen experienced a 41.86% decrease in income per trip, a 59.19% reduction in crew wages per trip, and a 38.16% increase in fuel consumption per trip. The Net Present Value (NPV) decreased from IDR 456,251,850 before reclamation to IDR 141,900,795 after reclamation. The Net B/C ratio dropped from 4.43 to 2.58, the Internal Rate of Return (IRR) declined to 30.22%, and the payback period extended by 1.13 years. NTN analysis showed a decline of 0.22 or 22.44% compared to pre-reclamation conditions. Adaptation strategies involve relocating fishing grounds and continuing fishing activities. Proposed alternative policies include increasing vessel size, providing fuel quota subsidies, and fisher relocation.